Development of Lectora Inspire Based Learning Media to Improve Learning Outcomes of Light and Its Properties - Puspita Maya Sari; Dewi Nilam Tyas (Postgraduate, University of Mataram, 2024)
This research aims to determine the feasibility of Lectora Inspire-based learning media based on assessments from media experts and material experts; determine the effectiveness of using Lectora Inspire media in science subjects. This type of research is research and development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. At the development stage, learning media is tested for suitability through the assessment of 1 media expert and 1 material expert. Next, the implementation stage goes through two stages, namely small-scale testing and large-scale testing. The results of the research show that the level of media appropriateness based on the assessment of media experts is in the very feasible category with a score of 91.66%, while based on the assessment of material experts it is in the category very decent with a score of 88.46%. The significance level obtained is 0.004 on a small scale and 0.00 on a large scale, which means there is a significant difference. Meanwhile, the level of effectiveness obtained on a small scale is 70% and on a large scale it is 62%, which means that the media is in the quite effective category. Therefore, the Lectora Inspire learning media is very suitable and quite effective for use in science learning, light and its properties